Pulmonary Nocardiosis in the Immunocompetent Host: Case Series - Inderjit Singh; Frances Mae West; Abraham Sanders; Barry Hartman; Dana Zappetti (Case Reports in Pulmonology)
Pulmonary nocardiosis is commonly recognized as an opportunistic infection in patients with predisposing immunosuppressive conditions. However, reports of pulmonary nocardiosis in the immunocompetent host are rare. Here, we report a case series of four patients with pulmonary nocardiosis without a predisposing condition.